OPTIMALISASI BAURAN PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA KENDARAAN RODA EMPAT DI KOTA URBAN - Bima Rizky Ananda; Tiara Oktasari; Moses Moses; Marinus Gea; Jeny Kristiani Gea; Udin Ahidin (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
During the last ten years, there has been an increase in the use of four-wheeled vehicles, especially in urban cities. It is not surprising that there are many vehicle showrooms everywhere, bidding on car sales, both new and used. This condition has increased the intensity of competition among four-wheeled business actors, thus demanding more effort in winning business competition. Based on this phenomenon, in fact this research was conducted, to see and analyze the effectiveness of the marketing mix in increasing used car sales in urban/Tangerang cities. The method used to express these problems is quantitative. That is, the research was carried out statistically, by disclosing field data in an informative and relevant manner, thereby obtaining a statement showing the level of effectiveness of a marketing mix used. To obtain research data, questionnaires were distributed to 100 respondents. This research was conducted in one of the car showrooms, namely Dwi Perkasa Mobiltama, South Tangerang. In translating the research data, a statistical analysis based on estimation/regression was used, in order to obtain the required information. In the analysis stage, measurable efforts are carried out in the form of testing the truth and reliability of the data, testing the prerequisites for regression, and testing the hypothesis. The research results obtained information, that the most effective marketing mix in increasing sales is the product/car quality aspect. This confirms, in the four-wheeled automotive industry, product quality is the main assessment for consumers in purchasing. They will only buy cars that are really good to drive, comfortable, and provide adequate safety.